The impact of chemotherapy dose adjustment and delay in patients with leukemias and lymphomas who exercise - Szymański, Bartłomiej; Piaszczyński, Szymon; Płeska, Kacper; Wojtania, Joanna; Łepik, Michał; Uszok, Zofia; Rosiak, Krzysztof; Reguła, Kacper; Waloch, Kamil; Czajka, Andrzej (Quality in Sport, 2024)
This review addresses the critical challenge of leukemia and lymphoma, delving into the epidemiology, treatment adherence, impact of physical activity, and the pressing need for more effective chemotherapy protocols. The purpose is to synthesize current knowledge, highlight existing gaps, and emphasize the importance of innovation in patient care strategies. Epidemiological data show variability in incidence rates and underscore the roles age, genetics, and lifestyle play in disease risk and progression. These insights are vital for effective prevention and timely intervention. The focus of the discussion revolves around the development of chemotherapy protocols. Tailoring these to the individual’s genetic and cancer profile can lead to significant gains in efficacy and minimize unwanted side effects, crucially improving patient quality of life and compliance. Treatment adherence is fundamental to successful outcomes, requiring multifaceted support strategies. Education, side-effect management, and addressing care barriers are pivotal in ensuring patients fully benefit from therapy. Personalization in chemotherapy protocol development is a current focus, aiming to maximize efficacy while minimizing side effects to improve quality of life and survival. The conclusion advocates for an integrated approach combining research and clinical practice to cater to the biological intricacies of both the malignancy and the patient. Progress in these areas proclaims a future where personalized, effective, and compassionate cancer treatment is the norm, pushing us closer to the goal of transforming cancer into a manageable condition.